Creating employee readiness to gain support for change - Bapuuroh, Cyracus Badinye (International Journal of Scientific Research and Management (IJSRM), 2019)
The purpose of this study is to investigate how employee readiness for change was created during an organizational transformation in the telecommunication industry of Ghana. The research embraced a qualitative multiple case study using two companies. Data was gathered primarily through interviews from twenty employees. Thirteen (13) employees were interviewed from Airtel Ghana Ltd and seven (7) employees were interviewed from MTN Ghana Ltd. Managers and non-managers were the participants for the interviews. Semi-structured interviews were carried out. Thematic analysis was undertaken. It is established that: communication, explaining the need for change, engaging and addressing concerns of staff, reference to success stories, assurance about company’s capability, appropriateness of change, and team building were the tools used to create readiness for change. This research has strengthened knowledge in change management in the area of overcoming resistance to change that has been established over the years. This is the first time such a study has been carried out in Ghana especially in the telecommunications industry.